Leaf aging effects on copper and cadmium transfer along the lettuce-snail food chain. (November 2018) - Wang, Yi-Min; Zhang, Hui; Xiong, Yu-Ting; Zhu, Qian; Ding, Yu-Chen; Zhao, Shuai; Zhang, Xiao-Hui; Uchimiya, Minori; Yuan, Xu-Yin
Abstract: Metal bioavailability at root plasma membrane surfaces and chemical forms within cells putatively controls the trophic transfer processes. Accumulation and distribution of Cu or Cd in lettuce were investigated as a function of lettuce leaf aging through soil-solution culture experiments. Metal contents in snail tissues were examined after fed on young (interior) or old (exterior) age leaves for 15d, respectively. In both roots and leaves, Cu accumulation was higher than Cd by 3–90 fold. Regardless of 9.42 μmoL/L CuCl2 exposure, young leaves accumulated more Cu than old leaves, while higher Cu contents are found in snail tissues fed on old leaves. Opposite trends were observed for Cd. Copper as an essential element had a higher transfer factor (TF) than the non-essential element Cd in biomagnification from leaf to snail. Reasons involved in metal chemical forms within leaf cells, where higher percentages of toxicity and migration associated metal (Fi: inorganic form, Fii: water-soluble form and Fiii: pectate- and protein-integrated form) are found for Cu in old leaves (88.3–91.6%) and Cd in young leaves (86.8–94.5%). Metal activities at root plasma membrane surfaces (M 2+ 0 ) and chemical forms in Fi + Fii + Fiii linearly correlated with metal accumulation in lettuce and snail tissues ( R 2 > 0.900, p < 0.001 for snails fed on old leaves). Our study incorporated both the chemical form approach and M 2+ 0 into evaluating the trophic bioavailability of different metals along the lettuce-snail chain, which is important for mechanistic understanding of metal behaviors in the ecosystem. Graphical abstract: Image 1 Highlights: Different from Cd, young leaves accumulated more Cu than old leaves. Higher Cu contents in snail fed on old leaves, while it was opposite for Cd. Migration associated forms were higher for Cu in old leaves and Cd in young leaves. Both M 2+ 0 and metal in F(i)-F(iii) were well correlated with metal contents in organisms.